Use of Inter – Sector Approach in Teaching Specialists in Social Science anh Human in Vietnam – From Historical View - HIEP, Assoc. Prof. Dr. NGUYEN VAN; TRAM, Assoc. Prof. Dr. PHAM NGOC; ANH, MSc. PHAM THI VAN (The journal of contemporary issues in business and government, 2021)
In the current context, with the continuous development of digital technology 4.0 and AI, the social sciences and humanities majors need to change approaches in teaching, transformation and combine multi-method, interdisciplinary in teaching. Approaching from a historical perspective, the article analyzes the transformation and operation of the interdisciplinary approach in teaching and research in social sciences and humanities in Vietnamese universities. The above research results confirm that the interdisciplinary approach in teaching and research in the social sciences and humanities is an inevitable trend in the context of university autonomy in Vietnam and responds to the changing the world today.